Comprehension of elementary teacher education’s students as future teachers toward the implementation of the independent curriculum principles - Abdullah, Suhardi; Nurharyanto, Dwi Widyastuti; Hasanuddin, M. Irfan; Hasanuddin, M. Imran (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
This research is a qualitative descriptive study to measure students' level of comprehension in elementary teacher education at Khairun University toward implementing the principles of the independent curriculum. The independent curriculum makes it easy for teachers and students to conduct learning according to student's needs. Even though it has superior values ​​compared to the previous curriculum, the independent curriculum presents other problems. Therefore, understanding the principles of implementing the curriculum is essential to analyze so that the difficulties faced by students are immediately known as a preventive measure. The subjects of this research were 30 students in semester IV. The instruments used were tests and interviews. The test instrument consists of 36 description questions and an interview consisting of five main questions. Based on the test results, it was found that students needed to understand the implementation of the principles of the independent curriculum well. All students needed more understanding, starting from the learning components, implementation, and final evaluation. The interview results also strengthened the comprehension test results. Students said that limitations in seeking additional information and different learning and assessment processes confused them with the independent curriculum. One of the solutions is special training and assistance for students to develop independent curriculum products such as teaching modules or student worksheets as instruments in carrying out assessments.